Tradition and the Formation of the Talmud - Vidas, Moulie 1983- (Princeton Oxford Princeton University Press, 2014)
Tradition and the Formation of the Talmud offers a new perspective on perhaps the most important religious text of the Jewish tradition. It is widely recognized that the creators of the Talmud innovatively interpreted and changed the older traditions on which they drew. Nevertheless, it has been assumed that the ancient rabbis were committed to maintaining continuity with the past. Moulie Vidas argues on the contrary that structural features of the Talmud were designed to produce a discontinuity with tradition, and that this discontinuity was part and parcel of the rabbis’ self-conception. Both this self-conception and these structural features were part of a debate within and beyond the Jewish community about the transmission of tradition.Focusing on the Babylonian Talmud, produced in the rabbinic academies of late ancient Mesopotamia, Vidas analyzes key passages to show how the Talmud’s creators contrasted their own voice with that of their predecessors. He also examines Zoroastrian, Christian, and mystical Jewish sources to reconstruct the debates and wide-ranging conversations that shaped the Talmud’s literary and intellectual character.
Based on a thesis (Ph. D) Princeton University, 2009
Includes bibliographical references and index
Reproduktion
In English
Keywords: Religion -- Judaism -- General; Talmud -- History; Jewish Law -- Interpretation and construction; Jewish Law; Talmud; RELIGION / Judaism / Talmud; Amoraic tradition; Babylonian Talmud; Bava Qamma; Christian literature; Christian sources; Christianity; Christians; Hekhalot literature; Hekhalot tradition; Israel; Jewish culture; Jewish genealogy; Jewish history; Jewish people; Jewish tradition; Jews; Judaism; Mesopotamia; Oral Torah; Palestinian Talmud; Rav Yehuda; Sar ha-Torah narrative; Scripture; Torah study; Written Torah; Zoroastrian literature; Zoroastrian ritual; Zoroastrian sources; anonymous layer; apodictic rulings